Biomaterial Strategies for Stem Cell Maintenance During In Vitro Expansion - Yan, Xiang-Zhen (Mary Ann Liebert, Inc., 2014)
Stem cells, having the potential for self-renewal and multilineage differentiation, are the building blocks for tissue/organ regeneration. Stem cells can be isolated from various sources but are, in general, available in too small numbers to be used directly for clinical purpose without intermediate expansion procedures in vitro. Although this in vitro expansion of undifferentiated stem cells is necessary, stem cells typically diminish their ability to self-renew and proliferate during passaging. Consequently, maintaining the stemness of stem cells has been recognized as a major challenge in stem cell-based research. This review focuses on the latest developments in maintaining the self-renewal ability of stem cells during in vitro expansion by biomaterial strategies. Further, this review highlights what should be the focus for future studies using stem cells for regenerative applications.